HOUSEHOLDS DEMAND FOR GROUND WATER CONSERVATION: THE CASE OF IRRIGATION PRACTICES IN KOMBOLCHA DISTRICT, EASTERN ETHIOPIA - Fentaw, Saleamlak; Mazgebo, Alem (Economics of Agriculture, 2018)
Ground water degradation is the problem, and its management is curial for sustaining the benefit from the resource. To maintain the resource we have to have full information about the value of the resource conservation. Therefore, in this study a contingent valuation survey was conducted in Kombolcha district to elicit households willingness to pay for groundwater conservation. A sample of 394 households was randomly selected, and interviewed. However, after checked for sample selection bias 4 protest bidders were excluded from the data set. Tobit model was applied to determine the factors affecting willingness to pay. The descriptive analysis shows that about 82% of the respondents reported that the groundwater has being degraded due to population pressure, deforestation, soil degradation, agricultural expansion and climatic change. The mean willingness to pay was computed at 60.63 ETB with the total willingness to pay of 1,689,576.21 per annum. The study determined that monthly income, educational level, total farm land holding, total family size, perception and tropical livestock unit were variables that have significant effect on households willingness to pay. Thus, socio-economic variables should also be considered while designing water related projects at household level.